2023
DOI: 10.1038/s41467-023-36114-x
|View full text |Cite
|
Sign up to set email alerts
|

The H2A.Z and NuRD associated protein HMG20A controls early head and heart developmental transcription programs

Abstract: Specialized chromatin-binding proteins are required for DNA-based processes during development. We recently established PWWP2A as a direct histone variant H2A.Z interactor involved in mitosis and craniofacial development. Here, we identify the H2A.Z/PWWP2A-associated protein HMG20A as part of several chromatin-modifying complexes, including NuRD, and show that it localizes to distinct genomic regulatory regions. Hmg20a depletion causes severe head and heart developmental defects in Xenopus laevis. Our data ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…24,25,34−36 We set out to identify interaction partners of BEND3 by proximity labeling, which revealed NuRD complex subunits as in vivo BEND3 proximal proteins, further supporting a potential link between BEND3 and NuRD. 24,34,37,38 Despite this co-localization on chromatin, BEND3 does not impact the genome-wide localization of NuRD but regulates PRC2 recruitment to chromatin. 24,25 The exact mechanisms underlying these interesting observations remain elusive and further work is needed to unravel the complex relationship between BEND3, NuRD, and Polycomb.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25,34−36 We set out to identify interaction partners of BEND3 by proximity labeling, which revealed NuRD complex subunits as in vivo BEND3 proximal proteins, further supporting a potential link between BEND3 and NuRD. 24,34,37,38 Despite this co-localization on chromatin, BEND3 does not impact the genome-wide localization of NuRD but regulates PRC2 recruitment to chromatin. 24,25 The exact mechanisms underlying these interesting observations remain elusive and further work is needed to unravel the complex relationship between BEND3, NuRD, and Polycomb.…”
Section: ■ Discussionmentioning
confidence: 99%
“…We were intrigued by the fact that BEND3 is mainly known to be associated with the repression of gene expression, while it was recently shown that BANP is involved in the activation of gene expression . Previous studies suggest that BEND3 associates with repressive chromatin complexes, including NuRD. ,, We set out to identify interaction partners of BEND3 by proximity labeling, which revealed NuRD complex subunits as in vivo BEND3 proximal proteins, further supporting a potential link between BEND3 and NuRD. ,,, Despite this co-localization on chromatin, BEND3 does not impact the genome-wide localization of NuRD but regulates PRC2 recruitment to chromatin. , The exact mechanisms underlying these interesting observations remain elusive and further work is needed to unravel the complex relationship between BEND3, NuRD, and Polycomb. BEN domain-containing proteins are evolutionally conserved (the human genome encodes for 9 BEN domain-containing proteins), and although some of these proteins are important for chromatin biology, others are completely uncharacterized. , We anticipate that important insights into cellular functioning will be obtained by studying this relatively uncharacterized protein family.…”
Section: Discussionmentioning
confidence: 99%
“…Treated cells in HN conditions showed upregulated purine metabolism and collagen synthesis, and, interestingly, a component of kinetochore, Zwilch (Zwilch kinetochore protein) was upregulated. Also, Hmg20a, a critical regulator of muscle differentiation and regeneration [ 49 ], was upregulated. There are a few other interesting protein expression differences in cultured myotubes shown on the heatmap ( Figure A6 ), which might be useful as a starting point for other studies.…”
Section: Discussionmentioning
confidence: 99%
“…HN conditions treated cells showed up-regulated purine metabolism and collagen synthesis, and, interestingly, a component of kinetochore, Zwilch (Zwilch Kinetochore Protein) was up-regulated. Also, Hmg20a, a critical regulator of muscle differentiation and regeneration [49], was upregulated. There are a few other interesting protein expression differences in cultured myotubes shown on the heatmap ( Figure S6 ) which might be useful as starting point for other studies.…”
Section: Discussionmentioning
confidence: 99%